Impact of FLD Intervention on Yield, Adoption and Horizontal Spread of Oilseed Crops in Konkan - Mahesh Mahale , Sandeep Patil; Ashok Chavan (Indian Journal of Extension Education, 2016)
Frontline demonstrations were conducted in Lanja and Rajapur Taluka of Ratnagiri district during 2008 to 2012. Total 93 farmers from two villages namely Asage and Gawane for Groundnut and 26 farmers from Gawane village as poor crop demonstration were selected. The demonstrations were laid out on farmer’s field according to recommended package of practices of Dr Balasaheb Sawant Konkan Krishi Vidyapeeth, Dapoli. The farmers practice was considered as control plot in demonstration cluster. The results revealed that significant raise in yield of groundnut over the control by 60.15 per cent, 53.23 per cent, 47.00 per cent, 46.00 per cent and 74.00 per cent for the year 2007-08, 2008-09, 2009, 2009-10 and 2012, respectively. The yield of Niger was 2.75 q/ha in the year 2008-09 which was increased to 3.11 q/ha in the year 2009-10. The overall adoption level of groundnut production technology and Niger were increased by 181.72 per cent and 233.38 per cent respectevely, due to FLDs. The varieties of groundnut such as SB-11 and local were replaced by Konkan Tapora and Konkan Gaurav, and local variety of Niger was replaced by IGP76 & Phule Karala in demonstration cluster